Impact of weekly iron-folic acid supplementation on nutritional status and parasitic reinfection among school-age children and adolescents in Sub-Saharan Africa: a systematic review and meta-analysis - Kedir, Shemsu; Abate, Kalkidan Hassen; Mohammed, Bekri; Abafita, Jemal; Ademe, Beyene Wondafrash (Frontiers in Pediatrics, 2024)
Background Two significant etiological factors contributing to iron deficiency anemia, and undernutrition posing substantial public health challenges in Sub-Saharan Africa, are soil-transmitted helminths and malaria. This study carried out the effect of weekly iron-folic acid supplementation (WIFAS) on the nutrition and general health of school-age children and adolescents in Sub-Saharan Africa, a systematic review and meta-analysis have been conducted. Methods To find pertinent publications for this study, a thorough search was carried out on May 20, 2023, across five databases: Pubmed (MEDLINE), Web of Science, Scopus, Cochrane Library, and Google Scholar. In addition, a search was conducted on August 23, 2023, to capture any new records. The inclusion criteria for the studies were based on school-age children and adolescent populations, randomized controlled trials, and investigations into the effects of WIFAS. The outcomes of interest were measured through anthropometric changes, malaria, and helminthic reinfection. Results A systematic review of 11 articles revealed that WIFAS significantly decreased the risk of schistosomiasis reinfection by 21% among adolescents (risk ratio = 0.79, 95%CI: 0.66, 0.97; heterogeneity I2 = 0.00%, P = 0.02). However, no significant impact was observed on the risk of malaria reinfection (risk ratio = 1.02, 95%CI: 0.92, 1.13; heterogeneity I2 = 0.00%, P = 0.67) or A. Lumbricoides reinfection (risk ratio = 0.95, 95%CI: 0.75, 1.19; heterogeneity I2 = 0.00%, P = 0.65). Moreover, the analysis demonstrated that there is no significant effect of iron-folic acid supplementation in measured height and height for age Z-score (HAZ) of the school-age children (Hedge's g −0.05, 95%CI: −0.3, 0.2; test for heterogeneity I2 = 0.00%, P = 0.7) and (Hedge's g 0.12, 95%CI: −0.13, 0.37; test for heterogeneity I2 = 0.00%, P = 0.36) respectively. Conclusion The effectiveness of WIFAS in reducing the risk of schistosomiasis reinfection in adolescents has been demonstrated to be greater than that of a placebo or no intervention. Additionally, the narrative synthesis of iron-folic acid supplementation has emerged as a potential public health intervention for promoting weight change. However, there was no significant association between WIFAS and Ascariasis, trichuriasis, and hookworm. Moreover, the certainty of the evidence for the effects of WIFAS on height and malaria is low and therefore inconclusive. Whereas, the certainty of the evidence for the effectiveness of WIFAS on Schistosomiasis is moderate. Even though the mechanisms need further research WIFAS may be implemented as part of a comprehensive public health strategy to address schistosomiasis in adolescents. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023397898, PROSPERO (CRD42023397898).